Settlement Process on The Black Sea Northeastern Coast in the Context of Frederick Turner’s Frontier Concept (1830‑1850s) - Sergey N. Shapovalov (Журнал Фронтирных Исследований)
The article is based on documentary materials and examines the settlement process on the Black Sea northeastern coast in the 1830–1850s. The methodological basis of the study is F. Turner’s frontier conception. The attention is focused on the analysis of such conception’s provisions as: constant migration of the population, transformation of wild areas, pushing forward of the “tongues” of populated areas, using of state lands. This approach allows to identify similar and different processes that arose during the North American and North Caucasian border lands development. The aim of the paper is to study the settlement and development features of the Black Sea northeastern coast as one of the historical regions of the modern Krasnodar territory through the prism of F. Turner’s frontier concept. A comparison of the American development of border lands and the experience of Russian settlement of the Black Sea northeastern coast makes it possible to identify similar and different processes in the 1830–1850s. Russian migration to the frontier was controlled. The intensity of transformation of the wilderness was quite high. The development of the Russian borderland was also achieved by pushing forward the “tongues” of the populated areas. State lands were used to provide gratuitous land to Anapa and Trans-Kuban settlers. The article is intended for historians and anyone interested in the settlement of the Black Sea northeastern coast.